Guide to facilitate a theory of change reflection process toward low-emission food systems - Falk, Thomas (International Food Policy Research Institute, 2022)
The CGIAR Research Initiative on Low-Emission Food Systems (Mitigate+) will help low- and middle-income countries reduce food systems emissions without impeding progress toward development goals. Thereby, Mitigate+ uses an innovation systems approach. In close collaboration with partners, CGIAR researchers will develop and deploy evidence and tools to understand and untangle the complexities of the political, economic, cultural, and biophysical components of the food system’s greenhouse gas problem. To generate more impactful and demand-driven knowledge, the Initiative’s “place-based” participatory research will focus on working with stakeholders, including farmers and other actors of the local food systems, to collaboratively design, test, and deploy emission-reduction strategies. This approach is fundamentally different from top-down development models where “solutions” are designed and delivered without adequate participation from intended beneficiaries.